FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASIL PELAYANAN PADA PENERBITAN TANDA DAFTAR PERUSAHAAN (TDP) OLEH BADAN PELAYANAN DAN PENANAMAN MODAL (BPT-PM) KOTA PEKANBARU - Riri Jufriana; Harapan Tua R.F.S (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
services to the community, known as the public service (public service) in fact is a series of services performed by the apparatus of Government to all walks of life with the aim of meeting the needs of the community. The extent of the public service to be supplied by the Government cause not all government units able to provide satisfying service as desired by the community. As a man of the people, the Government apparatus should be able to improve continuously with the standard fast service. BPT-PM Pekanbaru is always seeking to improve the Ministry's smooth running and common tasks in the field of licensing and permissions. It can be seen from the fact that the CPM-PM Pekanbaru always awarded every year.The purpose of this research is to know the factors that affect the success of the Service Mark on publishing list of companies (TDP) by CPM-PM of Pekanbarucity. This research uses Qualitative, descriptive Methods, data gathering techniques by conducting observations and interviews in which the parties involved in the implementation of the public service in the CPM-PM Pekanbaru. Research using Standard community service theory advanced by Mahmudi.The results of this research suggests that the factors that affect the success of the Service Mark on publishing a list of companies (TDP) of CPM-PM Pekanbaru is already well underway, where service is already clear procedures, time of completion is already quite good, the appropriate service charge, product services, adequate infrastructure and facilities, the competence of the officers the giver of good service and adequate.Keywords: Service, Excellent Service